New Realities and Virtualities: Libraries' Changing Roles in the World of Digital Rights Management. - Collins, J. Stephanie; West, Carol T.; Chan, Tom; Movafaghi, Shahriar; Pournaghshband, Hassan (International Journal of the Book, 2011)
Libraries serve as repositories of human knowledge and accumulated information. When new intellectual works are produced, they are housed in libraries, for the purpose of sharing the content with as many different parties as possible, with the goal of creating universal accessibility to ideas. The production of a new intellectual work means that there are many stakeholders who will be affected by policies that govern its dissemination and use. These include authors, researchers, librarians, and audience members. Librarians are at the nexus of the conflicts that may arise between the various rights and desires that are attached to works of intellectual labor. Digital works have changed how libraries deal with intellectual property. With digital media, copyright laws cannot be enforced in the same manner as before. In response to these challenges, authors and publishers use Digital Rights Management (DRM) techniques to restrict how digital works can be used. This creates conflict between a library's mission and the desire of authors and publishers to control intellectual work. This conflict cannot be resolved by a single library for many reasons. This paper discusses ways that both authors' and audience members' rights can be preserved going forward. These include reconsideration of copyright laws, standardization of DRM practices, and other methods.